Print advertisements in Malaysia - Hashim, A. (Blackwell Publishing, 2010)
This paper examines print advertisements in Malaysia to determine how advertisers seek to achieve their primary goal of persuading or influencing an audience by the use of both language and visuals. It describes the main component moves and rhetorical strategies used by writers to articulate the communicative purpose of the genre and the language in the advertisements. A descriptive framework for multi-modal texts is adopted for analysing the visuals. How the advertisements encode national identity and cultural values, and illustrate innovative language use is shown. The findings illustrate the multilayered and competing values from various sources in the Malaysian society and reinforce the traditional as well as the new values based on national, global or commercial priorities.